2018
DOI: 10.1177/2309499017754107
|View full text |Cite
|
Sign up to set email alerts
|

Fracture lines and comminution zones in OTA/AO type 23C3 distal radius fractures: The distal radius map

Abstract: Objective: This study was designed to define fracture lines and comminution zones in OTA/AO 23C3 distal radius fractures from axial computed tomography (CT) images that would influence surgical planning, development of new classifications, and possible implant designs. Methods: Thirty-four consecutive OTA/AO 23C3 fractures treated by a single surgeon between January 2014 and December 2014 were analyzed. For each fracture, maps of the fracture lines and zones of comminution were drawn. Each map was digitized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…Fracture mapping is an imaging method used to examine fracture characteristics and morphology [7]. It allows for the quantitative evaluation of fractures based on CT images and has already been used for investigating scapular fractures, Hoffa fractures and distal radius fractures [7][8][9][10]. The aim of this study is to use fracture mapping on distal radius fractures of AO/OTA type 23C3 and test the null hypothesis that fracture fragments can be divided according to Melone's classification (shaft, radial styloid, the dorsal medial fragment, and volar medial fragment) [5].Given the limited information available on the anatomical patterns of articular comminution in C3 fractures, this study also aimed to introduce heat mapping of fracture lines to evaluate the morphology of comminuted distal radius fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture mapping is an imaging method used to examine fracture characteristics and morphology [7]. It allows for the quantitative evaluation of fractures based on CT images and has already been used for investigating scapular fractures, Hoffa fractures and distal radius fractures [7][8][9][10]. The aim of this study is to use fracture mapping on distal radius fractures of AO/OTA type 23C3 and test the null hypothesis that fracture fragments can be divided according to Melone's classification (shaft, radial styloid, the dorsal medial fragment, and volar medial fragment) [5].Given the limited information available on the anatomical patterns of articular comminution in C3 fractures, this study also aimed to introduce heat mapping of fracture lines to evaluate the morphology of comminuted distal radius fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture mapping technique described by Cole et al 14 was applied in this study to evaluate the fracture patterns of AO/OTA 34 C3 multifragmentary patellar fractures. To the best of our knowledge, this technique has been used to identify the fracture patterns of complex articular fractures, including scapular fractures 15 , pilon fractures 14 , tibial plateau fractures 16,17 , posterior malleolar ankle fractures 18 , Hoffa fractures 19 , distal radius fractures 20 , and quadrilateral plate fractures 21 . However, this is the rst study to analyze the articular fracture patterns systemically in the coronal and sagittal views to improve the understanding of complex articular injuries of the patella.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several surgeons said that fracture MT could optimize preoperative planning, such as surgical approach and setting specificity fixation structure [8], [10], [11], [14], [15], [16], [17], [18], [19] , [20], [21]. Others said that the understanding of fracture patterns through the MT of fractures leads to the possibility of the development of new classifications and implant designs [22]. Many others thought that two-dimensional or three-dimensional fracture MT can illustrate the characteristics of fracture distribution and help surgeons predict specific types of fracture injuries (n=9, 32.14%), and lastly some found that MT can also predict the number of fracture lines and the direction of fracture lines, which may have a certain impact on treatment [23].…”
Section: Data Synthesismentioning
confidence: 99%